2006
DOI: 10.2136/sssaj2003.0285
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Reflectance Methodology in Comparison to Traditional Soil Analysis

Abstract: Traditional soil analyses are expensive, time‐consuming, and may also result in environmental pollutants. The objective of this study was to develop and evaluate a methodology to measure soil attributes using spectral reflectance (SR) as an alternative to traditional methods. Tropical Brazilian soils were sampled over a 196‐ha area divided into grids. Samples (n = 184) were obtained from the 0‐ to 20‐ and 80‐ to 100‐cm depths and georeferenced. The laboratory SR data were obtained using a Spectroradiometer (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(156 citation statements)
references
References 30 publications
7
132
1
16
Order By: Relevance
“…Coleman et al (1993) started with 0.4 R² for clay using Landsat. Nanni and Demattê (2006) reached 67 % accuracy for the clayey class when evaluated an area with full exposure of non-vegetated areas (bare soils). Demattê et al (2009) reached 90 % accuracy evaluating 224 pixels in a 300,000 ha area, but in this case, it was all done in a single image.…”
Section: Theoretical Validation Stage (Soil Surface Texture Classificmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman et al (1993) started with 0.4 R² for clay using Landsat. Nanni and Demattê (2006) reached 67 % accuracy for the clayey class when evaluated an area with full exposure of non-vegetated areas (bare soils). Demattê et al (2009) reached 90 % accuracy evaluating 224 pixels in a 300,000 ha area, but in this case, it was all done in a single image.…”
Section: Theoretical Validation Stage (Soil Surface Texture Classificmentioning
confidence: 99%
“…In particular, many studies have found that texture can be quantified by spectral reflectance under laboratory conditions (Nanni and Demattê, 2006). Nanni et al (2012) have also observed the importance of orbital images for clay estimates.…”
Section: Introductionmentioning
confidence: 99%
“…This 182-ha area, at altitudes between 475 and 567 m asl, is bordered by low lands along the course of the Rio Capivari; it had already been studied by Nanni & Demattê (2006) and is used for sugar cane production. The regional climate is Cwa (mesothermic with dry winters), according to the Köppen classification.…”
Section: Study Areamentioning
confidence: 99%
“…The local geology is dominated by the Itararé Formation, where siltstones are common, alternated with diabase dikes and sills from the Serra Geral Formation (Mezzalira, 1966), pleistocenic and holocenic fluvial sediments along the Rio Capivari terraces (Nanni & Demattê, 2006), and hardened siltstone areas near the diabase, due to contact metamorphism.…”
Section: Study Areamentioning
confidence: 99%
“…In many recent studies, the application of remote sensing techniques has gained much attention, mainly because these techniques have been shown to generate faster and cheaper characterizations, earning them credibility in the scientific community. The application of remote sensing techniques in soil studies began in the 1960s (Bowers & Hanks, 1965) and expanded to various applications, including quick and nondestructive quantification of soil attributes (Janik et al, 1998;Shepherd & Walsh, 2002, Dunn et al, 2002ViscarraRossel, et al, 2006a;Demattê & Nanni, 2006;Brown, et al,. 2006), soil survey and classification (Demattê et al, 2004, Ben-Dor et al, 2008, mineralogical measurements (Madeira-Netto, 1996;Viscarra-Rossel et al, 2006b;Sellito et al, 2009), digital soil mapping (Viscarra-Rossel & McBractney, 2008), precision agriculture (Thomasson et al, 2001Mouazen et al, 2007) and quantification of heavy metals (Wu Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%